ANALISIS KINERJA KARYAWAN DITINJAU DARI PELATIHAN, MOTIVASI KERJA, DAN KEPUASAN KERJA DI PT ASTRA INTERNASIONAL TBK AUTO 2000 WARU - Simanjuntak, Iola Riris; Santoso, Bowo (JURNAL LENTERA BISNIS, 2026)
This study aims to examine how job training, work motivation, and job satisfaction contribute to employee performance at PT Astra Internasional TBK Auto 2000 Waru. Because the focus is on sales and customer service, it is very important for the company to pay attention to employee performance and what factors support performance improvement for employee performance. The level of product sales quantity is a serious concern for employees, especially at the company. To 52 respondents who work at the Auto 2000 Waru company, a questionnaire with a Likert scale weight of 1-5 was given as a quantitative approach and respondent survey in this study. In analyzing and processing the data obtained, the Smart PLS application was used. The findings show that job training, work motivation, and job satisfaction contribute positively and significantly to improving employee performance. This finding indicates that these variables play a crucial role in increasing employee productivity contributions in the company environment.